Patrimônio e turismo: um estudo da aplicação de diretrizes e diplomas legais no município de Sorocaba-SP - Capati, Natália Simôes (Universidade Federal de São Carlos, 2009)
The theme of this survey is the analysis of public guidelines existing for the preservation of the cultural heritage in the country, and how they are applied to two cases in Sorocaba city. The main purpose is to compare them in terms of legal apparatus and tourist activity elements in this scenario. The survey would to show that tourism is not usually present in Sorocaba cultural heritage and often his managers not realise the tourism, in special the cultural tourism as a tool for the preservation of historical heritage. In addition to bibliographic search in the area, Oral history was used as a supplementary methodology to obtain data, besides the field visit. The procedure followed was analyse the role of public managers responsible for heritage (Federal, State and municipal) and the heritage policies, based on historical and cultural significance of the objects of study chosen - in this case, São Bento monastery and Bom Jesus do Bonfim chapel, allied to some considerations of cultural tourism potentiality in the city.
Heritage and tourism: a study of the application of legal guidelines and diplomas in the municipality of Sorocaba-SP
Keywords: Patrimônio; Turismo cultural; Mosteiro de São Bento e Capela do Senhor Bom Jesus do Bonfim; Cultural Heritage; Cultural Tourism; São Bento Monastery and Bom Jesus do Bonfim Chapel; CIENCIAS SOCIAIS APLICADAS::TURISMO